2020
DOI: 10.1126/sciadv.abc6250
|View full text |Cite
|
Sign up to set email alerts
|

Enoxacin induces oxidative metabolism and mitigates obesity by regulating adipose tissue miRNA expression

Abstract: MicroRNAs (miRNAs) have been implicated in oxidative metabolism and brown/beige adipocyte identity. Here, we tested whether widespread changes in miRNA expression promoted by treatment with the small-molecule enoxacin cause browning and prevent obesity. Enoxacin mitigated diet-induced obesity in mice, and this was associated with increased energy expenditure. Consistently, subcutaneous white and brown adipose tissues and skeletal muscle of enoxacin-treated mice had higher levels of markers associated with ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 60 publications
0
16
0
2
Order By: Relevance
“…Overall, these results suggested that the contribution of microbiota on AZI's metabolic influences was limited in our study. Interestingly, a recent report shows that the quinolone Enoxacin also exhibited direct effects on adipose tissues but not via microbiota 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these results suggested that the contribution of microbiota on AZI's metabolic influences was limited in our study. Interestingly, a recent report shows that the quinolone Enoxacin also exhibited direct effects on adipose tissues but not via microbiota 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that bactericidal antibiotics, including Ciprofloxacin (quinolone), Ampicillin (β-lactam), and Kanamycin (aminoglycoside), lead to breakdown of tricarboxylic acid (TCA) cycle and electron transport chain (ETC) and consequently increased oxidative stresses in epithelial cells 30 . On the other hand, Enoxacin (another quinolone) induced intrinsic oxidative metabolism in a beneficial way, which resulted in enhanced TCA cycle, downregulation of mir-34a-5p and increased FGF21 signals, and eventually increased beige adipogenesis and ameliorated obesity 32 . Besides, recent work showed that Doxycycline (tetracyclines) prevented cell death and inflammation in severe mitochondria disease (MD) mutant cells and complex I deficiency (Ndufs4 -/- ) mice featuring Leigh syndrome by inducing mitohormetic response in neuronal system 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Thermogenesis through exogenous activation, such as treatments of certain plant extracts (e.g., Rutin), cytokines (e.g., IL-22), may provide an alternative option ( Hu et al, 2017 ; Qi et al, 2019 ). A recent study has found that enoxacin induces thermogenesis and prevents obesity by regulating miR-34a-5p expression in adipose tissue ( Rocha et al, 2020 ). However, it is unknown whether these functions exist in DHEA-induced PCOS model and achieve the desired therapeutic effect of ameliorating reproductive and endocrine dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Enoxacin is a broad-spectrum fluoroquinolone antibacterial agent that has been officially approved by the U.S. Food and Drug Administration for treating urinary tract infections ( Rocha et al, 2020 ). In addition, as a stimulator of RNA interference and microRNA activity, enoxacin also displays some biological effects on tumor growth or bone disease ( Melo et al, 2011 ; Cornaz-Buros et al, 2014 ; Liu et al, 2014 ; Zhao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation